ASSESSMENT OF ANGIOSPERMIC FLORA AT RAJSHAHI METROPOLITAN AREA OF BANGLADESH - KHANOM, FARHANA; RAHMAN, A H M MAHBUBUR (Innovare Journal of Life Sciences, 2023)
Objectives: The study aimed to document the angiospermic flora at Rajshahi metropolitan area of Bangladesh. The study also examined the species diversity in the study area. Methods: The research work is based on fresh materials collected during 33 field visits at Rajshahi metropolitan area of Bangladesh was carried out from February 2016 to March 2017 to cover the seasonal variations. Plant parts with either flower or fruits collected using traditional herbarium techniques to make voucher specimens for documentation. Results: The results show that a total of 494 species belonging to 455 genera and 106 families were recorded. Of these, Magnoliopsida (Dicotyledones) is represented by 413 species under 390 genera and 84 families while Liliopsida (Monocotyledones) is represented by 81 species under 65 genera and 22 families. For each species scientific name, local name, family name, habit, relative occurrence, and flowering time were recorded. The present study will help in identifying the major angiospermic plant species for further investigation. Conclusion: The present research focused on the angiospermic flora growing throughout the Rajshahi metropolitan area of Bangladesh. A total of 494 angiospermic plant species were recorded.